FINANCE AND INEQUALITY: HOW DOES GLOBALIZATION CHANGE THEIR RELATIONSHIP?. (4th June 2013) - Kunieda, Takuma; Okada, Keisuke; Shibata, Akihisa
<x content-type="archive" xml:space="preserve">Abstract</x> This research demonstrates that international financial integration changes the way in which financial development affects inequality within a country. Specifically, both cross-country analysis and dynamic panel data analysis using data collected from more than 100 countries provide evidence indicating that if the financial market of a country is strongly closed to the world market, financial development narrows inequality within that country, whereas if the financial market of a country is strongly open to the world market, financial development widens inequality within that country. Our theoretical framework provides a possible explanation for our empirical findings.